Peningkatan Hasil Belajar Siswa Menggunakan Model Problem Based Intruction (PBI) Tema 8 pada Siswa Kelas IV SDN 001 Samarinda Utara - Parende, Uri’ Sinta; Pane, Widi Syahtia (SISTEMA: Jurnal Pendidikan, 2020)
This research is a Class Action Research (PTK) aimed at improving the learning outcomes of the theme of 8 Areas where I Live through the application of Problem Based Intruction (PBI) learning models in grade 4 students at SDN 001 Samarinda Utara in the 2018/2019 Learning Year. This research was conducted at SDN 001 Samarinda Utara with a research subject of grade IV B students, consisting of 30 students consisting of 12 female students and 18 male students. Each cycle is held 2 meetings, where each end of the learning is evaluated in the form of a written test to find out the student's learning results. Data collection techniques are carried out in the form of written tests, observations, documentation and interviews. The results showed that in cycle I, cycle II, and cycle III there was an increase. The average learning result of cycle I is in Bahasa Indonesia 54.1, IPA 37.6, SBdP 60. In the second cycle the average learning result is on the Content of Bahasa Indonesia 72.5 IPA 66, SBdP 100. In the third cycle the average value is in Bahasa Indonesia content 86.2, IPA 79.6, SBdP 100. Based on the results of the research, it can be concluded that the Problem Based Intruction (PBI) learning model can improve the learning outcomes in grade 4 students at SDN 001 North Samarinda.